Renal angiofibroma: A case report - Wei Chen, M.D; Carmen J. Julius, M.D; Robin M. Elliott, M.D (Elsevier, 2018)
A 28 year-old woman presenting with abdominal pain was found by CT scan to have a 5.7 cm mass in the right kidney. Examination of the nephrectomy specimen revealed a tumor with histopathologic features consistent with angiofibroma, an entity heretofore described only the nasopharynx, genital region, and somatic soft tissue.